2021
DOI: 10.3390/jcm10194343
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Could Predict Outcome in Patients Presenting with Acute Limb Ischemia

Abstract: Introduction: Acute limb ischemia (ALI), classified according to Rutherford’s classification (RC), is a vascular emergency burdened by high rates of mortality and morbidity. The need of new and different prognostic values for ALI has emerged, and, among all, the neutrophil-to-lymphocyte ratio (NLR) has been proven as a strong outcome predictor in vascular disease. The aim of this study is to investigate the role of preoperative NLR in predicting clinical outcomes in patients presenting acute limb ischemia. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…Elevated NLR and PLR levels in peripheral artery disease have been linked to increased amputation rates, severe cardiovascular events, and death [ 32 , 33 ]. High values of these ratios were also associated with poor outcomes in the evolution of specific diseases, such as abdominal aortic aneurysm (AAA), chronic threatening limb ischemia (CTLI), and other cardiovascular emergencies [ 13 , 27 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These biomarkers also proved to be predictive in oncology and oncological surgery, particularly in colorectal cancer, pancreatic cancer, gastric cancer, and cardiology and cardiac surgery [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated NLR and PLR levels in peripheral artery disease have been linked to increased amputation rates, severe cardiovascular events, and death [ 32 , 33 ]. High values of these ratios were also associated with poor outcomes in the evolution of specific diseases, such as abdominal aortic aneurysm (AAA), chronic threatening limb ischemia (CTLI), and other cardiovascular emergencies [ 13 , 27 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. These biomarkers also proved to be predictive in oncology and oncological surgery, particularly in colorectal cancer, pancreatic cancer, gastric cancer, and cardiology and cardiac surgery [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the most extensively studied biomarker is NLR, without associating the other biomarker in acute scenarios. The most recent papers regarding the predictive role of NLR in ALI are that of Taurino et al [ 27 ], Tasoglu et al [ 28 ], and Pasqui et al [ 29 ], who established that an NLR > 5 NLR was strongly associated with poor outcomes in ALI patients.…”
Section: Introductionmentioning
confidence: 99%
“…NLR can perform risk stratification and prognosis assessment for patients with ACS. Previous studies have also shown that NLR is not only a reliable marker of mortality and amputation stratification in patients with acute limb ischemia, but also an independent prognostic factor for the 30-day morbidity of ruptured abdominal aortic aneurysms (rAAA) (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Teperman et al found that elevated NLR was an indicator of severe multilevel PAD (35). In another study by Taurino et al, the authors found that preoperative NLR level was related to acute limb ischemia outcomes in unselected population (36). Importantly, NLR is easy to obtain and can be directly calculated based on the data of blood cell counts in routine laboratory tests of patients, without increasing the medical expenses of patients and the workload of doctors.…”
Section: Discussionmentioning
confidence: 99%